DETERMINATION OF INULIN FROM MULTIVITAMIN SYRUP PRODUCT BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY WITH RI DETECTOR - Yuni Retnaningtyas (Indonesian Journal of Chemistry, 2012)
At present, inulin is often added to multivitamin syrup product. The determination of the component of preparation both qualitatively and quantitatively is important to ensure quality of the product. This research is aimed to develop a high performance liquid chromatography method to analyze inulin in multivitamin syrup preparation. Separation of inulin from the sample, was performed using Aminex column HPX-87H (300 x 7.8 mm) Ion Exclusion at a temperature of 80 °C with isocratic elution system using deionized water as mobile phase at a flow rate of 0.5 mL/min, and detected by using refractive index detector. This method validation showed a good linearity with correlation coefficient (r) of 0.999 while the coefficient of variation of the regression function (Vx0) was 2.00%. The limit of detection (LOD) and the limit of quantification (LOQ) of the method were respectively 0.12 mg/mL and 0.37 mg/mL. The mean absolute recovery of inulin from the simulation sample was 99.42% and the method precision was less than 2%. The proposed method has been applied to the determination of inulin in commercial multivitamin syrup and the recovery of label claim was 99.9 mg/100 mL. The proposed HPLC method is rapid, simple, and selective for routine analysis.